2008
DOI: 10.1002/mnfr.200700296
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mammary tumor progression in a transgenic mouse model fed an isoflavone‐poor soy protein concentrate

Abstract: Dietary exposure to soy has been associated with reduced breast cancer incidence. Soy isoflavones and protein components, such as protease inhibitors and the lunasin peptide, have been indicated as potential agents reducing carcinogenesis. In this study, the effect of soy-based diets was evaluated in a transgenic mouse model of breast carcinoma, overexpressing the neu oncogene. Neu female mice were fed for 20 wk a soy- and isoflavone-free diet (IFD), 4RF21 laboratory mouse diet, soy-based, thus isoflavone-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Bioactive components present in soy foods, specifically the soy isoflavone genistein (GEN) have been a focus of our studies given the many health benefits attributed to dietary soy intake (Dong and Qin 2011;Jin and MacDonald 2002;Chiesa et al 2008;Caan et al 2011;Shu et al 2009). These beneficial effects are considered to be particularly manifest in the lower risk of breast cancer reported for Asian women who consume soy-based foods as part of their regular diets beginning in early life (Korde et al 2009;Dong and Qin 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive components present in soy foods, specifically the soy isoflavone genistein (GEN) have been a focus of our studies given the many health benefits attributed to dietary soy intake (Dong and Qin 2011;Jin and MacDonald 2002;Chiesa et al 2008;Caan et al 2011;Shu et al 2009). These beneficial effects are considered to be particularly manifest in the lower risk of breast cancer reported for Asian women who consume soy-based foods as part of their regular diets beginning in early life (Korde et al 2009;Dong and Qin 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies administering soy diets to transgenic mice have also shown conflicting results. A study by Chiesa et al [ 44 ] fed MMTV-neu transgenic mice a diet high in soy protein and soy isoflavones during gestation and lactation. At weaning, mice received a soy-free diet, a diet high in soy protein and soy isoflavones or a diet high in soy protein but containing low levels of soy isoflavones.…”
Section: Discussionmentioning
confidence: 99%
“…One study using MMTV- neu mice found that mice fed a diet containing the isoflavone-enriched product, Prevastein, had reduced tumor incidence and prolonged tumor latency in the group that were fed a high-fat diet based on corn oil, but not in the group with a diet based on fish oil. Meanwhile, the other study found no impact on tumor incidence in MMTV- neu transgenic mice fed a high soy diet compared to controls [95]. In the study using MTB-IGFIR mice, tumor incidence was increased and tumor latency was decreased in MTB-IGFIR mice fed a diet containing 20% ISP compared to casein-fed MTB-IGFIR mice [66].…”
Section: Mammary Tumor Development Following Lifetime Soy Isoflavomentioning
confidence: 99%